Inherent Noise‐Aware Insect Swarm Simulation. (17th January 2014) - Wang, Xinjie; Jin, Xiaogang; Deng, Zhigang; Zhou, Linling
<x xml:space="preserve">Abstract</x> Collective behavior of winged insects is a wondrous and familiar phenomenon in the real world. In this paper, we introduce a highly efficient field‐based approach to simulate various insect swarms. Its core idea is to construct a smooth yet noise‐aware governing velocity field that can be further decomposed into two sub‐fields: (i) a divergence‐free curl noise field to model noise‐induced movements of individual insects in a swarm, and (ii) an enhanced global velocity field to control navigational paths in a complex environment along which all the insects in a swarm fly. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>